Impact of COVID-19 on foodborne illness in Africa - A perspective piece - Helen Onyeaka; Ifeanyi Michael Mazi; Iyiola Olatunji Oladunjoye; Esther Ibe Njoagwuani; Hope Akegbe; Omotosho Adeola Dolapo; Ogueri Nwaiwu; Phemelo Tamasiga; Chidinma Ezinne Ochulor (Elsevier, 2023)
Food safety investments in Africa, through international donors or national programs, were primarily focused on the formal market sector. However, increasing consumer food safety concerns about foods sold in the growing informal food markets, the rising foodborne disease burden in Africa, and the emergence of COVID-19 have all made food safety a major concern and ultimately brought it to an inflection point in Africa. In addition, Data on foodborne disease outbreaks revealed a scarcity of reported cases before and during the pandemic. The lack of information on foodborne disease reporting in Africa translates into one of the reasons why food safety in Africa is becoming a rising subject matter. This perspective discusses the situation of food safety in Africa before and after the COVID-19 pandemic. Finally, challenges confronting ongoing efforts to improve food safety in the post-COVID era in Africa are summarized and highlighted.